Surface roughness modeling for CNC end milling using artificial neural network - Al Hazza, Muataz Hazza Faizi; Adesta, Erry Yulian Triblas (2013)

(untitled)
This research presents the effect of high cutting speed on the surface roughness in the end milling process by using the Artificial Neural Network (ANN). An experimental investigation was conducted to measure the surface ro ughness for end milling. A set of sparse experimental data for finish end milling on AISI H13 at hardness of 48 HRC have been conducted. The artificial neural network (ANN) was applied to simulate and study the effect of high cutting speed on the surface roughness.